PERAN PEMERINTAH DALAM MENINGKATKAN KESEHATAN DAN PENCEGAHAN PENYAKIT MENULAR - Arifin, Jajang (Universitas Wiralodra, 2023)
Health is a basic need of every individual community that must be met by every nation and country. Including the state's obligation to protect its people from contracting diseases that are considered dangerous. The state as the largest organization is expected to be able to provide maximum services to overcome certain diseases, because the state has authority that covers the entire life of society. This research uses a doctrinal legal research model with a statutory approach method. Research results: 1. In fact, the Government is obliged to carry out efforts to prevent Infectious Diseases in accordance with Law No. 36 of 2009 concerning Health in article 152: (a) The Government, Regional Government, and District/City Government are responsible for implementing efforts to prevent, control, and eradicate infectious diseases; (b) The Government, Regional Government, and District/City Government are responsible for providing facilities, infrastructure, medicines, and vaccines in efforts to prevent, control, and eradicate infectious diseases; etc; 2. The national health system (SKN) reflects the efforts of the Indonesian nation to increase the ability, willingness and awareness to achieve the highest degree of health as a manifestation of general welfare, the government formulates the National Health System (SKN) policy reflects the efforts of the Indonesian nation to increase the ability, willingness and awareness to achieve the highest degree of health as a manifestation of general welfare.